Improving infrastructure in the United Kingdom - Pisu, Mauro (OECD Economics Department Working Papers, 2015)
The United Kingdom (UK) has spent less on infrastructure compared to other OECD countries over the past three decades. The perceived quality of UK infrastructure assets is close to the OECD average but lower than in other G7 countries. Capacity constraints have emerged in some sectors, such as electricity generation, air transport and roads. Developing and regularly updating a national infrastructure strategy, with the National Infrastructure Plan being a welcome first step in this direction, would contribute to reduce policy uncertainty and tackle capacity constraints in a durable way. The design of coherent development plans by local authorities congruent with the national and local planning systems should continue to improve project delivery. The government intends to finance a large share of infrastructure spending to 2020 and beyond through private capital. Unlocking private investment in a cost effective and transparent way could be supported by further improving incentives for greenfield investment, continuing to carefully assess and record public-private partnerships, and promoting more long-term financing instruments. This Working Paper relates to the 2015 OECD Economic Survey of the United Kingdom (www.oecd.org/eco/surveys/economic-survey-united-kingdom.htm)